Adaptogenic and Anxiolytic Effects of Ashwagandha Root Extract in Healthy Adults: A Double-blind, Randomized, Placebo-controlled Clinical Study - Salve, Jaysing (Cureus, 2019)
Background Stress, anxiety and impeded sleep are a frequent feature of life in modern societies. Across socio-economic strata, stress, anxiety and ineffective sleep detract from healthful living and serve as precursors of various ailments. The use of herbs to offset these antecedents and outcomes has greatly increased in recent years. Ashwagandha, an adaptogenic Ayurvedic herb, has been often used to combat and reduce stress and thereby enhance general wellbeing. While there have been other studies documenting the use of Ashwagandha for stress resistance, this is the first study to use a high-concentration root extract while also varying the dosage substantially. Therefore, this is the first study to offer insight into dose-response of a high concentration root extract. Material and methods In this eight-week, prospective, randomized, double-blind, placebo-controlled study, the stress-relieving effect of Ashwagandha root extract was investigated in stressed healthy adults. Sixty male and female participants with a baseline perceived stress scale (PSS) score >20 were randomized to receive capsules of Ashwagandha extract 125 mg, Ashwagandha extract 300 mg or identical placebo twice daily for eight weeks in a 1:1:1 ratio. Stress was assessed using PSS at baseline, four weeks and eight weeks. Anxiety was assessed using the Hamilton-Anxiety (HAM-A) scale and serum cortisol was measured at baseline and at eight weeks. Sleep quality was assessed using a seven-point sleep scale. A repeat measures ANOVA (general linear model) was used for assessment of treatment effect at different time periods. Post-hoc Dunnett’s test was used for comparison of two treatments with placebo. Results Two participants (one each in 250 mg/day Ashwagandha and placebo) were lost to follow-up and 58 participants completed the study. A significant reduction in PSS scores was observed with Ashwagandha 250 mg/day (P < 0.05) and 600 mg/day (P < 0.001). Serum cortisol levels reduced with both Ashwagandha 250 mg/day (P < 0.05) and Ashwagandha 600 mg/day (P < 0.0001). Compared to the placebo group participants, the participants receiving Ashwagandha had significant improvement in sleep quality. Conclusion Ashwagandha root aqueous extract was beneficial in reducing stress and anxiety.